Establishment of a new nuclear medicine facility: fundamental structure and their shielding - Rahman, A; Rabbani, ATMM; Biman, TA; Haider, MM; Khan, NI; Hossain, MN (Bangladesh Journal of Physics, 2020)
This work was an attempt to propose a model to set up for newly establishment of Nuclear Medicine facility. Medical physicist should establish a major guideline to set up a model of a new nuclear medicine facility; draw the fundamental structure and calculate the corresponding shielding. The various layouts such as the diagnostic (In-Vivo and In-Vitro) and therapeutic layouts of fundamental structure were been made on the primacies as controlled, supervised and non-supervised area according to radiation exposure rate. Some shielding calculations of various facilities such as the diagnostic and therapeutic facility have to provide on instrumentation and radiation safety with the required layout according to maximum activity of radionuclide into the controlled area. Bangladesh Journal of Physics, 26(2), 41-49, December 2019